2014
DOI: 10.14310/horm.2002.1520
|View full text |Cite
|
Sign up to set email alerts
|

NGAL and cystatin C: two possible early markers of diabetic nephropathy in young patients with type 1 diabetes mellitus: one year follow up

Abstract: OBJECTIVE: Diabetic nephropathy constitutes a major long-term complication in patients with type 1 diabetes mellitus (T1D) and its diagnosis is based on microalbuminuria. The aim of this observational follow-up study was to explore the role of neutrophil-gelatinase-associated lipocalin (NGAL) and cystatin C in unravelling early diabetic nephropathy even in patients with normoalbuminuria. DESIGN: Fifty-six euthyroid patients with T1D, with mean age 13.1 (SD: 3.2) years, and 49 healthy controls with mean age 12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Moreover, kidney injury was confirmed by significant increase in both serum cystatin C and NGAL levels. The significant correlation between NGAL, cystatin C and glomerular filtration rate decline supported the prognostic role of both markers in revealing early structural renal damage before an overt renal impairment becomes evident22. Diabetic mice receiving EGCG showed no significant alteration in BUN level compared to diabetic and normal mice which indicates that the animals were not in a lethal condition as the elevation in BUN is known to have a negative impact on survival23.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, kidney injury was confirmed by significant increase in both serum cystatin C and NGAL levels. The significant correlation between NGAL, cystatin C and glomerular filtration rate decline supported the prognostic role of both markers in revealing early structural renal damage before an overt renal impairment becomes evident22. Diabetic mice receiving EGCG showed no significant alteration in BUN level compared to diabetic and normal mice which indicates that the animals were not in a lethal condition as the elevation in BUN is known to have a negative impact on survival23.…”
Section: Discussionmentioning
confidence: 69%
“…In previous studies, NGAL was reported as effective in the early diagnosis of acute kidney injury (AKI) in several clinical settings [2325] and was also validated as a significant prognostic factor in cardiovascular morbidity [26]. The association between the early tubular lesions in nonalbuminuric patients with T1D and NGAL was further supported by recently published studies [18, 19, 21]. …”
Section: Introductionmentioning
confidence: 79%
“…Several studies have reported that nonalbuminuric subjects, including prepubertal children with long-standing diabetes, often have glomerular basement membrane (GBM) thickening, mesangial expansion [15, 16], and significant glomerulopathy lesions [17, 18]. Glomerular and renal tubular interstitial injury plays a role in the pathogenesis of DN [19], and various tubular markers have been assessed in the early detection of DN [10, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Venous blood specimens were collected from diabetic patients and controls into two sorts of vacutainer tubes as follows: first venous blood sample was collected in plain tube and left to clot for (30min) at room temperature and then centrifuge to separate at (3000rpm) for (10min) utilized for the biochemical examines. Second tube with EDTA, mixed gently by the shaker and then centrifuged to separate the plasma for 15min at 1000xg (2)(3)(4)(5)(6)(7)(8) …”
Section: Methodsmentioning
confidence: 99%
“…Tubular excretion of NGAL associates with the acuteness of chronic kidney failure, as in autosomal dominant polycystic renal disease or glomerulonephritis. [7,8] Haptoglobin is a hemoglobin-binding protein existing in the plasma. Its function is principal to control the destiny of hemoglobin out from red platelets after either extravascular or intravascular hemolysis.…”
Section: ]mentioning
confidence: 99%